P466 Acetarsol is an effective and safe option in the management of refractory ulcerative colitis. (16th January 2018) - Argyriou, K; Ingram, R J M; Blatt, R; Wilson, P; Samuel, S; Hawkey, C; Moran, G W
Abstract: Background: Acetarsol is an organic-based arsenic compound historically used to treat bacterial vaginal infections. Small preliminary cohort studies have suggested good clinical efficacy data for acetarsol in ulcerative colitis (UC). Mesalazine-refractory proctitis remains a clinical problem with superior topical therapy warranted. Our aim was to study the effectiveness and tolerability of acetarsol suppositories in a cohort of UC patients. Methods: In November 2017, we performed a retrospective cohort study by prospectively reviewing maintained clinical records for all patients exposed to acetarsol at the IBD clinic in Nottingham University Hospitals from 2004 through to 2015. Response was determined as a clinical improvement in symptoms or improvement in endoscopic appearance. Serum arsenic and C-reactive protein levels were reviewed when available. Data are presented as median and interquartile range. Results: Thirty-six patients were prescribed acetarsol suppositories (28 with proctitis, 6 with left-sided colitis, 1 with diversion colitis and 1 with chronic pouchitis). Twenty-one were males with an age of 42.5 (11) years and disease duration of 5 (17) years. All patients had failed mesalazine or corticosteroid-based topical therapy with 12 (33.3%) refractory to immunotherapy and 3 (8.3%) refractory to anti-TNF therapy. Acetarsol 250 mg bd for at least 4 weeks was prescribed in 69.4% of the cases. Median treatment duration was 12 weeks (18). Twelve patients were exposed to acetarsol more than once. 79.4% of patients achieved a clinical response. Eight of 36 patients had an endoscopic assessment with four of eight patients showing endoscopic improvement. 41.2% patients required further treatment escalation following acetarsol exposure with two patients needing a subtotal colectomy. Three patients (8.3%) stopped acetarsol due to side effects. One patient experienced vomiting, palpitations and sweating, and the other two experienced flushing and paresthesia. Arsenic level was 398.7 (418.8) nmol/l (<130 nmol/l). Serum arsenic levels were not correlated with patient clinical response nor to the need for treatment escalation. Conclusions: Acetarsol suppositories could be an effective and tolerable option in the management of refractory ulcerative proctitis. A definitive study is urgently warranted to thoroughly investigate the clinical efficacy and safety of this promising drug in UC.